1991
DOI: 10.1212/wnl.41.7.1088
|View full text |Cite
|
Sign up to set email alerts
|

Cervical dystonia

Abstract: We studied 300 patients, 61% women, with mean age 49.7 years and mean duration of dystonia 7.8 years, to determine the demographic and clinical characteristics of cervical dystonia (CD) and its relationships to other movement disorders. Torticollis was present in 82%, laterocollis in 42%, retrocollis in 29%, and anterocollis in 25%; however, the majority (66%) had a combination of these abnormal postures. Scoliosis was present in 39%, local pain reported by 68%, and 32% had evidence of secondary cervical radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
266
7
12

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 399 publications
(311 citation statements)
references
References 1 publication
26
266
7
12
Order By: Relevance
“…This could explain why we found only one case of family history in the HT+ group. A previous report 2 showed that there was a higher frequency of dystonia and tremor in relatives of patients with dystonia. We found a higher prevalence of postural hand tremor in HT+ group.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…This could explain why we found only one case of family history in the HT+ group. A previous report 2 showed that there was a higher frequency of dystonia and tremor in relatives of patients with dystonia. We found a higher prevalence of postural hand tremor in HT+ group.…”
Section: Methodsmentioning
confidence: 86%
“…It is often associated with other movement disorders, particularly tremor. some consider that essential tremor and idiopathic dystonia may be genetically linked 2 . The mechanism underlying CD and head tremor is unknown, but its association is frequent as assessed with other studies 3 .…”
mentioning
confidence: 99%
“…The relationship between scoliosis and dystonia seems to be reinforced by their association in human clinic. Patients with idiopathic cervical dystonia, a most frequent focal dystonia, develop scoliosis in 39% of cases [37]. Furthermore, scoliosis develops in late childhood or early puberty more frequently among patients with cervical dystonia [38].…”
Section: Discussionmentioning
confidence: 99%
“…In these patients pain is frequent and prominent, occurring in 66-85%. 4,5 Many patients have a limited range of neck motion. 4 Up to a third develop premature spondylosis 6,7 with accompanying radiculopathy and rarely myelopathy.…”
Section: Introductionmentioning
confidence: 99%